PENGARUH CITRA RUMAH SAKIT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN - Dian Fitriana; Djoko Wijono (Bajang Institute, 2023)
This study aims to determine the effect of hospital image and service quality on customer satisfaction, the effect of customer satisfaction on customer loyalty, the effect of hospital image and service quality on customer loyalty, and the effect of hospital image and service quality on customer loyalty through customer satisfaction. The research method in this research is the explanatory quantitative method. The population in this study were patients at the UII Bantul hospital with a total sample of 50 respondents. The validity test uses the product moment formula while the reliability test uses Cronbach's alpha. Meanwhile, data analysis in this study uses path analysis. The results of the study show that: (1) hospital image and service quality have a positive effect on customer satisfaction with path coefficient values of 0.419 and 0.382. (2) customer satisfaction positively affects customer loyalty with a path coefficient of 0.285. (3) hospital image and service quality have a positive and significant effect on customer loyalty with path significance values of 0.306 and 0.347 (4) hospital image and service quality have no positive and significant effect on customer loyalty through customer satisfaction with path coefficient values of 0.119 and 0.108 . This means that customer satisfaction is not able to mediate the effect of hospital image and service quality on customer loyalty.